Successful Treatment of Life Threatening Intracranial AVM by Endovascular Embolization in Dhaka Medical College Hospital (Journal of Medicine, 2010)
Arteriovenous malformations (AVMs) are tangled, dilated blood vessels in which arteries flow directly into veins. AVMs can bleed or directly compress brain tissue; seizures or ischemia may result. Haemorrhagic stroke from AVM represents 2% of all haemorrhagic strokes. A clear understanding of the diagnostic and treatment algorithms of cerebral AVM management is very important because AVMs are a cause of hemorrhage in young adults. We report a 16 years old boy with cerebral arteriovenous malformation (AVM), complicated by recurrent throbbing headache, vomiting and seizure. This was clearly diagnosed by Digital subtraction angiogram (DSA). He was successfully treated by endovascular embolization at Dhaka Medical College Hospital. This was the second successful cerebral endovascular embolization in any government hospital of Bangladesh. Keywords: Arteriovenous malformation, seizure, digital subtraction angiogram, endovascular embolization. DOI:10.3329/jom.v11i1.4275 J Medicine 2010: 11: 60-62